2001
DOI: 10.1089/109662001753165701
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Properties of Cucumariosides from the Edible Far-Eastern Holothurian Cucumaria japonica

Abstract: Holothurian triterpene glycosides (cucumariosides) are known to possess multiple biological activities. Here we show that cucumariosides from the Far Eastern edible holothurian (sea cucumber), Cucumaria japonica, and their semisynthetic derivatives possess potent immunomodulatory properties. Intraperitoneal injection of cucumariosides (0.2-20 ng per mouse) induced macrophage lysosomal activity in a dose-dependent manner (up to 250% of control). The stimulatory effect was related to the chemical structure of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 9 publications
3
41
0
1
Order By: Relevance
“…Similar results were reported by Miamoto et al They demonstrated that the desulfated derivatives inhibit more significantly tumor cell growth than glycosides with C-6 sulfates in monosaccharide units [26]. In comparison to anti-cancer activity, the macrophage lysosomal activity and increase of intracellular Ca ++ concentrations were also demonstrated to be related to chemical structures of Cucumariosides and be influenced by the number and positions of sulfate groups in the carbohydrate moiety of the molecules [27,28]. On the other hands, Cucumarioside A 2 -2 was the most active in inducing a rapid increase in cytosolic Ca ++ content, when compared to the polysulfated derivative of A 2 -2 [28].…”
Section: Cytotoxic Effects Of Frondoside a And Cucumariosidessupporting
confidence: 82%
See 2 more Smart Citations
“…Similar results were reported by Miamoto et al They demonstrated that the desulfated derivatives inhibit more significantly tumor cell growth than glycosides with C-6 sulfates in monosaccharide units [26]. In comparison to anti-cancer activity, the macrophage lysosomal activity and increase of intracellular Ca ++ concentrations were also demonstrated to be related to chemical structures of Cucumariosides and be influenced by the number and positions of sulfate groups in the carbohydrate moiety of the molecules [27,28]. On the other hands, Cucumarioside A 2 -2 was the most active in inducing a rapid increase in cytosolic Ca ++ content, when compared to the polysulfated derivative of A 2 -2 [28].…”
Section: Cytotoxic Effects Of Frondoside a And Cucumariosidessupporting
confidence: 82%
“…Our study also indicated that the acetyl group at C-16 of the aglycone in Frondoside A may play a significant role in Frondoside A cytotoxicity since Frondoside A has more potent effects than Cucumarioside A 2 -2 on cytotoxicity, cell cycle changes and apoptosis [13]. Similarly, monosulfated Cucumariosides A 2 -2 and A 4 -2 were among the most active compounds for stimulating peritoneal macrophage lysosomal activity, while desulfation of their carbohydrate moiety completely abolished this activity [27]. However, they demonstrated that lysosomal activity and cytoxicity of cucumariosides depends on structures of both aglycone and carbohydrate chain but there is no direct correlation between two activities of the glycosides [34].…”
Section: Cytotoxic Effects Of Frondoside a And Cucumariosidessupporting
confidence: 53%
See 1 more Smart Citation
“…*Correspondence: ketharani@gmail.com modulatory activities due to the presence of compounds such as sulponamides and diketones (Aminin et al, 2001). Many Asians believe sea cucumbers should be eaten to treat ailments such as cancer and arthritis, as well as intestinal and urinary dysfunctions (Purcell, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The effect was seen at picogram doses of cucumariosides with a maximum stimulation around 20 ng/mouse (Aminin et al 2001).…”
Section: Sea Cucumber Triterpene Glycosides Immunomodulatory Propertiesmentioning
confidence: 96%